Structural studies of the factor X activating complex of the intrinsic pathway of blood coagulation. - Atkins, Judith Sharron. (University of Ottawa (Canada), 1992)
In the blood coagulation pathway the zymogen factor X (FX) is converted to its enzymatic form (FXa) by the FX activating complex which is a membrane bound multi-protein complex comprised of the cofactor factor VIII (FVIII), the enzyme factor IXa (FIXa), the substrate FX, as well as calcium and phospholipid. Activation of FX to FXa is essential for production of fibrin, which is the final product of the coagulation pathway. Defects or deficiencies in FVIII or FIXa hinder production of FXa and results in the bleeding disorder, haemophilia. The data demonstrated that both chains of FVIII; FVIII light chain (FVIII-LC) and FVIII heavy chain (FVIII-HC), contained binding domains for FIXa. Binding of FIXa to FVIII-LC was observed to be mediated by hydrophobic forces, whereas divalent cation-dependent forces mediated binding to FVIII-HC. FVIII-LC was also found to contain a binding domain for FX. This interaction occurred independently of FVIII-HC and was maintained by hydrophobic forces. FVIII-LC contained hydrophobic binding domain(s) for phospholipid. Hydrophobic forces were also found to play a heretofore unrecognized role in the association of FIXa or FX with phospholipid. These data indicate that multiple forces are involved in forming and maintaining the integrity of the FX activating complex. Data from radioligand binding studies suggested that FVIII acted as a high affinity binding protein for FX (K$\sb{\rm d}$ = 10$\sp{-8}$ M) on the surface of synthetic phospholipid membranes. The effect of platelet storage on binding of FX was also examined. Unstimulated platelets did not bind FX. In contrast, specific binding of FX to stimulated platelets (K$\sb{\rm d}$ = 10$\sp{-8}$ M) occurred when platelets had been stored for less than 4.5 hours from phlebotomy. The affinity of binding of FX to fresh platelets was not significantly affected by the presence of FVIII (K$\sb{\rm d}$ = 10$\sp{-8}$ M), nevertheless, the storage-dependent decline in platelet binding of FX was not observed in the presence of FVIII. The high affinity and lability of the FVIII-independent binding site suggests that FX binds to a specific, and as yet unidentified, platelet membrane component. (Abstract shortened by UMI.)
Keywords: Chemistry, Biochemistry.